Estimates of hip fracture incidence in Japan using the National Health Insurance Claim Database in 2012–2015 - Tamaki, J.; Fujimori, K.; Ikehara, S.; Kamiya, K.; Nakatoh, S.; Okimoto, N.; Ogawa, S.; Ishii, S.; Iki, M. (Osteoporosis international, 2019)
Summary Using the nationwide health insurance claims database, we found that the age-standardized hip fracture incidence rates in Japan indicated significant increase in males but no significant change in females during 2012–2015. The fracture risk in subjects aged 75–84 years indicated decrease in females but no change in males. Introduction Nationwide registry data on hip fractures have not yet been established in Japan. Using the newly developed National Database of Health Insurance Claims (NDB), which covers the entire Japanese population, we investigated the incidence rates of hip fractures and the associated regional differences. We also assessed the frequency of osteoporosis prescriptions, bone turnover marker (BTM) level, and bone mineral density (BMD) measurements. Methods The annual numbers of hip fractures, osteoporosis prescriptions, and BTM level and BMD measurements by prefecture from 2012 to 2015 were obtained from NDB data. We calculated the standardized claims-data ratio (SCR) in each prefecture. Results The age-standardized incidence rates from 2012 to 2015 indicated no significant change in females and significant increase in males ( p value for trend; 0.920, 0.002, respectively). The fracture risk decreased in females aged 75–84 years and indicated no increase in females aged 85–89 years during 2012–2015, while the fracture risk indicated no change in males aged 75–84 years and increased in males aged 85–89 years. The frequency of osteoporosis prescriptions, BTM level measurements, and BMD measurements in the general population in the corresponding period increased with statistical or marginal significance in females and males. West–east regional differences were observed in the incidence rates; the highest SCR values in the western prefectures were approximately double the lowest values in the eastern prefectures. Conclusions The age-standardized hip fracture incidence rates indicated no significant change in females and significant increase in males in Japan from 2012 to 2015.